Algoritm for surgical method of treatment at spine tumors - Radchenko, Volodymyr; Popov, Andriy; Petrenko, Dmytro; Nessonova, Marina (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The main goal of the primary and metastatic spinal tumors treatment are local control, preservation of weight bearing and protective function of the spine with improvement patients quality of life. Objective. To develop mathematical algorithm for selection of surgical treatment volume in spinal tumor cases. Methods. Spinal instability neoplastic score supplemented with additional signs such as ASIA scale, tumor type, epidural spinal cord compression scale by Bilsky, local kyphosis, adjacent vertebras lesions was used for the model developing. Point system that takes 9 signs has been tested in 237 metastatic spinal tumor patients. Cluster analysis for the decision tree development was applied. Results. It has been confirmed the hypothesis about decreasing surgical volume with higher SINS score. But, it was not defined which boundary indicator to define specific volume of the surgery is precise. Two patients clusters were defined, that have differences in the surgical volume, degree of tumor lesion, epidural compression and local kyphosis, neurological symptoms. Cluster I included 115 patients with higher score (severe condition, higher volume of the surgical intervention) in comparison with 122 patients from the cluster II. Decision tree for the surgical volume selection in spinal tumor patients has been developed. Conclusions. The most important signes that affect the choice of the surgical volume selection are: neurological symptoms, type of vertebra lesion, spinal stenosis and type of the surgery (radical vs palliative). Application of the developed decision tree in the clinical practise gives the opportunity to select appropriate volume of the surgical intervention in spinal tumor patient with the high significance level that provides satisfactory treatment outcome.